Comparison of autofluorescence and white-light bronchoscopies performed with the Evis Lucera Spectrum for the detection of bronchial cancers: a meta-analysis - Sun, Shuangshuang (Transl Lung Cancer Res, 2020)
BACKGROUND: Many recent studies have reported that autofluorescence bronchoscopy (AFB) has a superior sensitivity and decreased specificity in the diagnosis of bronchial cancers when compared with white-light bronchoscopy (WLB). We specifically analyzed the diagnostic performances of autofluorescence imaging video bronchoscopy (AFI) performed with the Evis Lucera Spectrum from Olympus, which is a relatively novel approach in detecting and delineating bronchial cancers, and compared it to the older WLB method. METHODS: We searched the PubMed, Embase, Web of Science, and CNKI databases from inception to July 12(th), 2018 for trials in which patients were diagnosed with lung cancer via concurrent or combined use of AFI and WLB. The included studies were required to have a histologic diagnosis as the gold standard comparison, and a sufficient amount of data was extracted to assess the diagnostic capacity. A 2×2 table was constructed, and the area under the receiver-operating characteristic curve (AUC) of AFI and WLB was estimated by using a stochastic model for diagnostic meta-analysis using STATA software. RESULTS: A total of 10 articles were eligible for the meta analysis, comprising 1,830 patients with complete data included in the analysis. AFI showed a superior sensitivity of 0.92 (95% CI, 0.88–0.95) over WLB’s 0.70 (95% CI, 0.58–0.80) with P<0.01, and a comparable specificity of 0.67 (95% CI, 0.51–0.80) compared with WLB’s 0.78 (95% CI, 0.68–0.86) with P=0.056. Egger’s test P value (0.225) demonstrated that there was no publication bias. CONCLUSIONS: Our research showed that in the evaluation of bronchial cancers, AFI was superior to conventional WLB. With its higher sensitivity, AFI could be valuable for avoiding misdiagnosis.